Sistem Kontrol Level Air Dengan Pengontrol PID - Rahmani, Salma; Rosana, Suci Aulia; Tian, Ghina Hanin (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2022)
One of the problems in the world industry is the water level control system. Water level control is carried out at the holding tank, which is a common problem when the water level in the holding tank is not known, and lack of monitoring of the holding tank can lead to storage space or tank emptying. This study aims to control the water level system so that it reaches the set water level level point. The methodology used is by utilizing the fluid system that enters the tank and can vary the speed of the water pump with a DC motor, this research is simulated using the MATLAB application. 4 types of control have been carried out, namely P, PI, PD, and PID controllers, this is to find out which controller is best applied to a water level control system. In this study, the PID controller has the best results because it has a fast rise time, no overshoot, settling time and small steady-state error. Using PID control, it is possible to maintain water level levels to achieve the required efficiency and productivity.